The European Union and military force governance and strategy - Norheim-Martinsen, Per M. (Cambridge University Press, 2013)
The Common Security and Defence Policy maps out how the EU - established primarily to be an economic organisation - can purposefully prepare for and apply the use of military force. This book will appeal to scholars and advanced students of European studies, international relations and strategic studies.